2019
DOI: 10.1016/j.celrep.2019.03.094
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of E93 Gene Expression Acts as the Trigger for Metamorphosis Independently of the Threshold Size in the Beetle Tribolium castaneum

Abstract: Body size in holometabolous insects is determined by the size at which the juvenile larva undergoes metamorphosis to the pupal stage. To undergo larva-pupa transition, larva must reach a critical developmental checkpoint, the threshold size (TS); however, the molecular mechanisms through which the TS cues this transition remain to be fully characterized. Here, we use the flour beetle Tribolium castaneum to characterize the molecular mechanisms underlying entry into metamorphosis. We found that T. castaneum rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
59
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 49 publications
(90 reference statements)
2
59
0
1
Order By: Relevance
“…A previous study has suggested that threshold size in T. castaneum might be regulated by 413 JH (Chafino et al, 2019). However, in that study, the threshold size was identified by starving 414 larvae at various sizes during the final instar and identifying the size above which the larva initiates metamorphosis.…”
Section: Jh Does Not Affect Threshold Size Of M Sexta 408mentioning
confidence: 94%
See 4 more Smart Citations
“…A previous study has suggested that threshold size in T. castaneum might be regulated by 413 JH (Chafino et al, 2019). However, in that study, the threshold size was identified by starving 414 larvae at various sizes during the final instar and identifying the size above which the larva initiates metamorphosis.…”
Section: Jh Does Not Affect Threshold Size Of M Sexta 408mentioning
confidence: 94%
“…In this weight range, hypoxia-treated larvae are above the threshold size 272 whereas 40% diet-fed larvae are below the threshold size. We found that myo expression was 273 significantly higher in the muscles of hypoxia-treated larvae than that of 40% diet-fed larvae 274 Previous studies have suggested that a decline in JH may underlie threshold size 281 attainment in other insects (Chafino et al, 2019). To determine whether JH affects threshold size 282 attainment in M. sexta, larvae were placed in hypoxic conditions during the third instar until 283 HCS and then treated with 10 µg methoprene, a JH analog, two days later.…”
mentioning
confidence: 90%
See 3 more Smart Citations